Fabrication of superhydrophobic surface by oxidation growth of flower-like nanostructure on a steel foil - Weng, Rui; Zhang, Haifeng; Yin, Liang; Rong, Wanting; Wu, Zhiwen; Liu, Xiaowei (RSC advances, 2017)
Energy saving has drawn attention all around the world. The fluidic drag reduction effect of superhydrophobic surfaces has been investigated both theoretically and experimentally. However, there has been little experimental analysis on the drag reduction of superhydrophobic steel surfaces. Here, we present a novel method to fabricate the superhydrophobic surface with a 3D flower-like micro-nanostructure on the steel foil using the method of high-temperature oxidation. The wettability of the oxide films can be easily changed from super hydrophilic to superhydrophobic with chemical modification. We measure the liquid/solid friction of the as-prepared superhydrophobic surface using the self-assembly system. The drag reduction ratio for the superhydrophobic steel surface is 20-30% at low velocity. The superhydrophobic steel surface has numerous technical applications in drag reduction field. A novel method to fabricate the superhydrophobic surface with a 3D flower-like micro-nanostructure on the steel foil was presented here. The surface shows good drag reduction effect and has numerous technical applications in drag reduction field.